Novel Non-Invasive Diagnosis of Bladder Cancer in Urine Based on Multifunctional Nanoparticles - Xu, Jinshan; Zeng, Shuxiong; Li, Jun; Gao, Li; Le, Wenjun; Huang, Xin; Wang, Guandan; Chen, Bingdi; Zhang, Zhensheng; Xu, Chuanliang (Frontiers in Cell and Developmental Biology, 2022)
Objectives: Tumor cells were reported to have perpetual negative surface charges due to elevated glycolysis, and multifunctional nanoprobes (Fe3O4@SiO2, mNPs) could attach onto tumor cells via opposite surface charges. We thus evaluated whether mixing mNPs with urine could improve the sensitivity of urine cytology test (UCT). Methods: We developed a novel UCT method by mixing urine with mNPs (Nano-cytology) to harvest more tumor cells during UCT procedures. The same voided urine sample were divided equally for Nano-cytology and UCT assay, and evaluated by cytopathologists in a blinded way. The accuracy of UCT, Nano-cytology, and combination of the two approaches (Nano-UCT) for detecting bladder cancer were determined. Results: Urine samples were prospectively collected from 102 bladder cancer patients and 49 non-cancer participants from June 2020 to February 2021 in Changhai hospital. Overall sensitivity of Nano-cytology assay was significantly higher than UCT assay (82.4% vs 59.8%, P< 0.01). Sensitivity for low- and high-grade tumors were 79.1% and 39.5% (P <0.01), 84.7% and 74.6% (P=0.25) for Nano-cytology and UCT, respectively. Specificity of Nano-cytology was slightly lower than UCT (89.8% vs 100%, P=0.022), which mainly caused by severe urinary tract infection. In addition, Nano-UCT showed increased sensitivity with 90.2% for overall patients, and 83.7% and 94.9% for low- and high-grade tumor, respectively. Conclusion: Nano-cytology assay had a significantly improved sensitivity compared with UCT for detecting bladder cancer patients. It represents a promising tool for diagnosis and recurrence surveillance of bladder cancer in clinical practice. Keywords: bladder cancer, diagnosis, nanoparticles, urine cytology